2018
DOI: 10.3758/s13421-018-0807-7
|View full text |Cite
|
Sign up to set email alerts
|

Don’t believe everything you hear: Routine validation of audiovisual information in children and adults

Abstract: Previous research has shown that the validation of incoming information during language comprehension is a fast, efficient, and routine process (epistemic monitoring). Previous research on this topic has focused on epistemic monitoring during reading. The present study extended this research by investigating epistemic monitoring of audiovisual information. In a Stroop-like paradigm, participants (Experiment 1: adults; Experiment 2: 10-year-old children) responded to the probe words correct and false by keypres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Richter et al (2009) found this interaction pattern in two experiments with true versus false statements. Further experiments have yielded epistemic Stroop effects for assertions of varying plausibility (Isberner & Richter, 2013) with belief-consistent and belief-inconsistent statements (Gilead et al, 2018), a nonlinguistic task (judging the color of a word; Isberner & Richter, 2013), a nonevaluative probe task (Isberner & Richter, 2014), and audiovisual information (Piest et al, 2018). These studies provide broad evidence for validation as a nonstrategic, involuntary process and for the assumption that validation produces implicit plausibility judgments and are more than mere disruptions of comprehension.…”
Section: Validation: Assessing the Plausibility Of Informationmentioning
confidence: 91%
See 1 more Smart Citation
“…Richter et al (2009) found this interaction pattern in two experiments with true versus false statements. Further experiments have yielded epistemic Stroop effects for assertions of varying plausibility (Isberner & Richter, 2013) with belief-consistent and belief-inconsistent statements (Gilead et al, 2018), a nonlinguistic task (judging the color of a word; Isberner & Richter, 2013), a nonevaluative probe task (Isberner & Richter, 2014), and audiovisual information (Piest et al, 2018). These studies provide broad evidence for validation as a nonstrategic, involuntary process and for the assumption that validation produces implicit plausibility judgments and are more than mere disruptions of comprehension.…”
Section: Validation: Assessing the Plausibility Of Informationmentioning
confidence: 91%
“…However, research systematically mapping out the conditions that affect validation is fairly new. The conditions examined to date include the contributions of world knowledge and contextual information (e.g., Isberner & Richter, 2014;van Moort, Koornneef, & van den Broek, 2018;Williams, Cook, & O'Brien, 2018), individual differences in working memory capacity and access to world knowledge (Singer & Doering, 2014), individual differences in beliefs (Gilead, Selal, & Marid, 2018), developmental influences (Piest, Isberner, & Richter, 2018), text genre (such as fantasy text: Creer, Cook, & O'Brien, 2018), and recency of text information (Guéraud, Walsh, Cook, & O'Brien, 2018).…”
mentioning
confidence: 99%
“…Recent evidence suggests that automatic validation of information takes place when a learner is presented with information from audiovisual modes, as previously established with textual information (Piest, Isberner, & Richter, 2018). Piest et al (2018) used a Stroop task to examine epistemic validation of audiovisual information. Participants saw an image and listened to a statement that was congruent, or not, with what was represented visually, and they immediately saw the words "Correct" or "False".…”
Section: Evaluation Of Multimodal and Multiple Informationmentioning
confidence: 97%
“…In this context, plausibility can be defined as the "acceptability or likelihood of a situation or a sentence describing it" (Matsuki et al, 2011, p. 926). Experiments with reaction times based on the epistemic Stroop paradigm in which false, belief-inconsistent, or implausible statements slow down affirmative responses in an unrelated task provide strong evidence for routine validation with various types of linguistic and audio-visual stimuli (e.g., Gilead et al, 2019;Isberner & Richter, 2013Piest et al, 2018;Richter et al, 2009).…”
Section: Validation As Implicit Assessment Of Plausibilitymentioning
confidence: 99%